An Effective Security Method Based on Combining 802.1x, DMZ and SSL-VPN for IoT Network Security - Kilincer, İlhan Firat; Ertam, Fatih; Yaman, Orhan; Şengür, Abdulkadir (My University, 2020)
IoT applications appear in many areas due to their flexible structures and many advantages they provide. The increase in IoT applications brings many security vulnerabilities. In order to close these security gaps and ensure the security of the created system, some measures should be taken by combining existing technologies with new technologies. In this study, a method that uses various security technologies together is proposed to ensure the security of the IoT application network. Accordingly, 802.1x technology was used to connect wireless sensor devices to a Wi-Fi network. Thus, in the first step, unauthorized users are not allowed to connect to this network. In the second step, IoT data was collected on a central server, and this server was taken to the DMZ zone in the firewall. Thus, access to the server is both restricted, and server access is logged. In the last step, with SSL-VPN configured in the firewall, data can be safely monitored from the external environment. The biggest advantages of the proposed approach are that it can be used easily in existing Wi-Fi networks, provides communication security, and is low cost. Considering these advantages, it is considered to be an important work in the field of IoT network security..
Keywords: Bilgisayar Bilimleri; Yazılım Mühendisliği